Hukum Lingkungan: Tanggung Jawab Pemerintah Daerah dan Peran Masyarakat dalam Pengelolaan Hutan Lindung Dikabupaten Bima - Owen, Muhammad Owen Setiawan; Ridwan; Aman Ma'arij (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to determine how the implementation of policies and regulations of the Bima Regency Government in the management of protected forests, as well as the obstacles faced, and to determine the extent of community participation in protecting protected forests in Bima Regency, as well as factors that influence community involvement. This research uses empirical legal methods with a qualitative approach and a case study in Bima District. Data was collected through in-depth interviews with stakeholders, field observations, and document studies (primary and secondary data) to analyze the implementation of protected forest management policies. This combination of approaches allows for an in-depth understanding of practices on the ground while producing contextualized policy recommendations. The results of this study indicate that the implementation of protected forest policy in Bima District faces challenges due to the imbalance between economic development and conservation. The focus on maize production in the RPJMD 2021-2026 triggered forest conversion, with 57% of the area degraded. Community participation is still limited at the implementation stage due to lack of incentives and dependence on forest products. Solutions are needed through: (1) economic-ecological policy balancing, (2) strengthening supervision, (3) alternative economic empowerment, and (4) community-based collaborative approaches. Without these measures, pressure on forests will continue to threaten environmental sustainability.